A good death from the perspective of healthcare providers from the internal medicine department in Shanghai: A qualitative study - Chunyan Chen; Xiaobin Lai; Wenjuan Zhao; Menglei Chen (Elsevier, 2022)
Objective: This study aimed to explore the understanding of healthcare providers working in the internal medicine department in Shanghai regarding a good death. Methods: The data of the study was collected using face-to-face semi-structured interviews. Through purposive sampling, 16 physicians and 13 nurses who had experiences of caring for adult patients with life-threatening illnesses at the end-of-life stage in Shanghai were interviewed. The interviews were analyzed using qualitative content analysis. Results: Six characteristics of a good death emerged: no suffering, companionship and care, no worries or concerns, dying with dignity, involvement and acceptance, and less impact on the family. Eighteen categories were identified: dying without experiencing suffering; being relieved of symptoms and suffering; being relieved of psychological suffering; avoiding the use of futile treatment and resuscitation; being cared for and accompanied by family; receiving good health care; having a meaningful life without regrets; making good arrangements for family issues; having a chance to say goodbye; having a quality life before death; dying in a decent environment; the personal will to be respected; maintaining the integrity of the body; death of the patient being accepted by the family and healthcare providers; the death occurred despite the best efforts to care for the patient; limited financial and care burden; shortly affected quality of life of the patient; and improved family cohesion. Conclusion: Family members' early involvement in caring for patients at the end-of-life stage helps achieve a good death. For patients with a terminal illness, avoiding unnecessary medical treatment and resuscitation could be the first step in achieving better patient death and promoting the development of advanced care planning in the mainland of China.